FENOTIPE VIRUS AVIAN INFLUENZA (AI) SUBTIPE H5N1 BERBEDA KARAKTER GENETIK DI INDONESIA - Dharmayanti, NLP Indi; Indriani, Risa; Hartawan, Risza; Ratnawati, Atik (Perhimpunan Biologi Indonesia, 2014)
In Indonesia, data on the phenotype of AI virus subtype H5N1 is very limited, due to the facilities for such testingshould be performed in a laboratory Biosafety level III. Additionally influenza virus has a high error rate duringtranscription of their genome has low RNA polymerase. High error rates generate quasispecies. In this study, wedid some H5N1 viruses infection with different genetic variations and conducted DNA sequencing in severalorgans. To determine the possible emergence detection of quasispecies in different organs and until the virus wasexcreted. We tested the hypothesis that the quasispecies might arise from virus that was infected to theexperimental animals. The results of this study showed that the AI virus subtype H5N1 had different phenotypes inanimal depending on their genetic character. AI virus subtype H5N1 killed chickens within 48-72 hoursdepending on the genetic character of the virus. New AI viruses of subtype H5N1 caused more severe organdamage severe than the character of the old AI viruses. Adaptation of virus in each organ also proved that the viruslikely create variations/quasispecies, which was different from the viral origin.Keywords: Phenotypes, avian influenza, H5N1, genetic character, quasispecies